The relationship between the net income of a company and its turnover, fixed assets and long term liabilities / Mazlina Mustapha - Mustapha, Mazlina (1992)
This project, paper is carried out. to figure out if there is any relationship between the net income of a company with its turnover, fixed assets and long term liabilities, and if there is a relationship, to what degree are they related. This research will be carried out., by using statistical techniques.